Statistical theory of branching morphogenesis - Hannezo, Edouard; Simons, Benjamin D. (Development, growth & differentiation, 2018)
Branching morphogenesis remains a subject of abiding interest. Although much is known about the gene regulatory programs and signaling pathways that operate at the cellular scale, it has remained unclear how the macroscopic features of branched organs, including their size, network topology and spatial patterning, are encoded. Lately, it has been proposed that, these features can be explained quantitatively in several organs within a single unifying framework. Based on large‐scale organ reconstructions and cell lineage tracing, it has been argued that morphogenesis follows from the collective dynamics of sublineage‐restricted self‐renewing progenitor cells, localized at ductal tips, that act cooperatively to drive a serial process of ductal elongation and stochastic tip bifurcation. By correlating differentiation or cell cycle exit with proximity to maturing ducts, this dynamic results in the specification of a complex network of defined density and statistical organization. These results suggest that, for several mammalian tissues, branched epithelial structures develop as a self‐organized process, reliant upon a strikingly simple, but generic, set of local rules, without recourse to a rigid and deterministic sequence of genetically programmed events. Here, we review the basis of these findings and discuss their implications. We review the basis of recent research activities that have developed and applied a unifying theory of branching morphogenesis in several mammalian tissues, including the mouse mammary gland epithelium, kidney and pancreas. We discuss the evidence in favor of the model, as well as the implications that these concepts have for the organization and function of ductal precursors.